2004
DOI: 10.1021/ja046871g
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Chiral Pyrrolidine−Pyridine Conjugate Base Catalysts for Use in Asymmetric Michael Addition Reactions

Abstract: Direct catalytic asymmetric Michael addition reactions of ketones to nitroolefins using newly developed chiral pyrrolidine-pyridine conjugate bases as catalysts are described. The desired 1,4-adducts are obtained in excellent yields with high enantio- and diastereoselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
109
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(114 citation statements)
references
References 19 publications
3
109
0
2
Order By: Relevance
“…Thus, 2-lithiopyridine, obtained by treatment of 2-bromopyridine with nbutyllithium, has been used in addition reactions to ketones, 91 nitriles, 92 amides 93 and the ring-opening of sulfamates. 94 Other substituted 2-pyridyllithium reagents have been obtained similarly and used recently in addition reactions to aldehydes, 95 Weinreb amides, 96 DMF, 97 and acyl chlorides, as in the reaction of the organolithium 30, prepared from 2-bromopyridine 29 by the typical exchange procedure, with pivaloyl chloride (Scheme 10). 98 The so-obtained ketone 31 is an intermediate in the synthesis of a chiral 2,2'-bipyridine oxide catalyst for enantioselective aldol reactions.…”
Section: Aromatic Six-membered Ringsmentioning
confidence: 99%
“…Thus, 2-lithiopyridine, obtained by treatment of 2-bromopyridine with nbutyllithium, has been used in addition reactions to ketones, 91 nitriles, 92 amides 93 and the ring-opening of sulfamates. 94 Other substituted 2-pyridyllithium reagents have been obtained similarly and used recently in addition reactions to aldehydes, 95 Weinreb amides, 96 DMF, 97 and acyl chlorides, as in the reaction of the organolithium 30, prepared from 2-bromopyridine 29 by the typical exchange procedure, with pivaloyl chloride (Scheme 10). 98 The so-obtained ketone 31 is an intermediate in the synthesis of a chiral 2,2'-bipyridine oxide catalyst for enantioselective aldol reactions.…”
Section: Aromatic Six-membered Ringsmentioning
confidence: 99%
“…Many compounds of succinamide and glutarimide are mentioned in clinical and preclinical analysis [5][6][7][8][9][10][11][12][13] . The substituted pyrrolidine is one of the structural subunits in natural compounds [14][15] . Several substituted pyrrolidine display important biological properties like anticancer 16 , inhibitors of alpha-glucosidase 17 , antimicrobial 18 and other applications [19][20][21][22][23][24][25] .…”
Section: Introductionmentioning
confidence: 99%
“…A related study by Enders showed a strong solvent effect in the reaction since in MeOH the enantioselectivity could be increased to 76% for the major syn diastereomer in the reaction between 3-pentanone and trans-β-nitrostyrene employing a 20 mol% of Lproline as catalyst. [7] Since these preliminary studies, very effective catalytic systems (2-20) [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] have been developed for the asymmetric Michael reaction of ketones with nitroalkenes being the process generally syn-selective (Scheme 1). Best improvements to this reaction have been mostly achieved using pyrrolidine-based catalytic derivatives.…”
Section: Introductionmentioning
confidence: 99%